Digital Laser Micropainting: Digital Laser Micropainting for Reprogrammable Optoelectronic Applications (Adv. Funct. Mater. 1/2021). (4th January 2021) - Lee, Younggeun; Kwon, Jinhyeong; Lim, Jaemook; Shin, Wooseop; Park, Sewoong; Hwang, Eunseung; Shin, Jaeho; Cho, Hyunmin; Jung, Jinwook; Kim, Hyun‐Jong; Han, Seungyong; Lee, Habeom; et al.
Abstract : In article number 2006854, Seung Hwan Ko, Sukjoon Hong, and co‐workers propose a digital laser micropainting technique, based on controlled thin‐film interference, through direct laser growth of the absorbing metal oxide layer on a metallic reflector. Specific wavelength‐dependent photoresponsivity can be assigned, erased, and reassigned to an optoelectronic device by the successive application of the proposed technique, which substantiates its potential for future reprogrammable optoelectronic applications.